2020
DOI: 10.5811/westjem.2020.2.45028
|View full text |Cite
|
Sign up to set email alerts
|

Presyncope Is Associated with Intensive Care Unit Admission in Emergency Department Patients with Acute Pulmonary Embolism

Abstract: Introduction: Syncope is common among emergency department (ED) patients with acute pulmonary embolism (PE) and indicates a higher acuity and worse prognosis than in patients without syncope. Whether presyncope carries the same prognostic implications has not been established. We compared incidence of intensive care unit (ICU) admission in three groups of ED PE patients: those with presyncope; syncope; and neither. Methods: This retrospective cohort study included all adults with acute, objectively confirmed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We included symptoms, signs, and findings likely to represent higher PE severity. As an example, we chose syncope instead of shortness of breath or chest pain based on clinical experience and evidence in the literature [31][32][33][34]. We added a variable that factored in initial heart rate < 50 or > 100 bpm [35].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…We included symptoms, signs, and findings likely to represent higher PE severity. As an example, we chose syncope instead of shortness of breath or chest pain based on clinical experience and evidence in the literature [31][32][33][34]. We added a variable that factored in initial heart rate < 50 or > 100 bpm [35].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…5,22,[33][34][35] At first glance, it is unsurprising that patients who arrived via EMS were sicker and had higher rates of 30-day all-cause mortality. How-ever, after adjusting for PE Severity Index class, Charlson Comorbidity score, troponin, BNP, and syncope or presyncope, 36 patients with acute PE who arrived by EMS were still less likely to be discharged within 24 h and more likely to die within 30 days. We found that EMS was an independent predictor of our 2 primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We translated those recommendations into explicit surveillance eligibility criteria, as described in eTable 1 in Supplement 1. We assumed that patients without a documented recent provocation for VTE (eg, major surgery or oral estrogen) had none—a reasonable assumption in our setting, given our medical record review experience that clinicians nearly always inquire about and document recent VTE provocations for patients with acute PE . We deemed the absence of VTE provocation as a contraindication to withholding anticoagulation because of increased risk for VTE recurrence .…”
Section: Methodsmentioning
confidence: 99%